Criminal Aspects of Illegal Online Lending Practices in Indonesia - Yanta Karona Subakti; Rospita Adelina Siregar (Universitas Muhammadiyah Palu, 2025)
The economic crisis, the increasing needs of society, and the development of the internet and digital world are seen as a golden opportunity for official banks and large financiers to gain greater profits. Banks that have existed so far provide loan facilities through applications and internet networks without collateral or guarantees and without complicated conditions. The interest is still affordable, the conditions are also in accordance with Bank Indonesia (BI) regulations and are under the supervision or supervision of the Financial Services Authority (OJK). In addition, there are also large investors, both individually and syndicated and in collaboration with banks that have made a financial technology (fintech) breakthrough in the form of providing online loan facilities or known to the public as